PISA Tests and their Impact on Georgian Education System - Tsiklauri, Mariam (Wydawnictwo Naukowe UAM, 2016)
The article discusses the PISA (Programme for International Student Assessment) tests and their impact on the Georgian Education System. It analyzes the deplorable results of Georgian 15-yearolds in PISA 2009 and investigates the reasons based on different reports. The article also discusses the reasons for the temporary suspension of the project on the Georgian side. Since certain participatory countries are dissatisfied with the attitudes of this program, the article also refers to the criticism of PISA. The conclusion is that PISA and other international tests contain considerably important information. If these data with a diagnostic feature are used for working out the education policy in an appropriate way, they can become the key instrument for obtaining favourable results in reforming the Education System. Therefore, PISA appears to be essential for Georgia too, as such assessment gives an opportunity to concentrate on the national core curriculum and content analysis. In order to estimate all the strengths and weaknesses of the Education System, it is quite reasonable to conduct such surveys in every country. The article concludes with recommendations for PISA 2015 as to how to use the reports for further progress.
Testy PISA i ich wpływ na system szkolnictwa w Gruzji
Keywords: international survey; education system; education reform; assessment; academic literacy; PISA